Awareness Raising Process in World Heritage Site Bursa - Başdemir, Ayten; Durmaçalış, Birben; Çalıkuşu, Eser; DOSTOĞLU, NESLİHAN (My University, 2016)
“UNESCO World Heritage and Bursa: Awareness Raising Project” has been developed by Bursa Site Management Unit with the contribution of educators, architects, and art historians. The project process, which started on 22 June 2014 with the inscription of Bursa in UNESCO World Heritage List, is still ongoing and is planned to continue in the future. The purpose of the project has been to create consciousness on cultural heritage in Bursa, to help local people recognize and embrace the values of Bursa, which have been accepted as World Heritage, and to contribute to the preservation of these assets in a sustainable way. Not only have various target groups been given training on the importance of preserving cultural heritage, but also consciousness has been raised on the meaning of being World Heritage through the wide use of the related logo, publication and distribution of books and brochures on this subject, and numerous presentations in various meetings.

“UNESCO Dünya Mirası ve Bursa: Farkındalık Yaratma Projesi” Bursa Alan Başkanlığı tarafından eğitimciler, mimarlar ve sanat tarihçilerinin katkılarıyla geliştirilmiştir. 22 Haziran 2014 tarihinde Bursa’nın UNESCO Dünya Miras Listesi’ne girmesi ile başlayan süreç günümüzde de devam etmekte olup, projenin gelecekte de sürdürülmesi planlanmaktadır. Projenin amacı Bursa’da kültürel miras konusunda farkındalık yaratmak, yerel halkın Bursa’nın Dünya Mirası olarak kabul edilmiş olan değerlerini tanımalarına ve benimsemelerine yardımcı olmak ve bu varlıkların sürdürülebilir bir şekilde korunmasınına katkıda bulunmaktır. Çeşitli hedef gruplara kültürel mirasın korunması üzerine eğitim verilmesinin yanısıra, ilgili logonun yaygın bir şekilde kullanılması, konuyla ilgili kitapların ve broşürlerin basılması ve dağıtılması, çeşitli toplantılarda çok sayıda sunum yapılması aracılığıyla Dünya Mirası olmanın anlamı üzerine farkındalık yaratılmıştır.
Dünya Miras Alanı Bursa'da Farkındalık Yaratma Süreci
Keywords: Awareness Raising; World Heritage Site; Bursa; Farkındalık Yaratma; Dünya Miras Alanı